HUBUNGAN EFIKASI DIRI DENGAN KECEMASAN AKADEMIK SISWA SEKOLAH MENENGAH ATAS DALAM MENJALANI PEMBELAJARAN DARING - Wahyuni, Ayu; Zukhra, Ririn Muthia; Woferst, Rismadefi (Coping: Community of Publishing in Nursing; Vol 11 No 2 (2023): April 2023, 2023)
Academic anxiety can have a negative impact on the quality of student learning. One of the things that effect the quality of student learning is self-efficacy. This study aims to determine the relationship between self-efficacy and academic anxiety of high school students in undergoing online learning. This study used a descriptive correlative design and aapproach cross sectional. The instrument used was a questionnaire containing questions about self-efficacy and academic anxiety that were valid and reliable. The research sample was 208 students at SMAN 8 Pekanbaru. Sampling using probability sampling technique, namely stratified non-random sampling. The analysis used is bivariate analysis using test chi-square. The results of this study indicate that most of the students very high self-efficacy were 111 students (53,4%) and students who had moderate academic anxiety were 139 students (66,8%). The results of statistical tests showed that there was a significant relationship between self-efficacy and academic anxiety of high school students in undergoing online learning with p value (0,000) < (0,05).